2017
DOI: 10.1534/genetics.117.300192
|View full text |Cite
|
Sign up to set email alerts
|

Integration of EGFR and LIN-12/Notch Signaling by LIN-1/Elk1, the Cdk8 Kinase Module, and SUR-2/Med23 in Vulval Precursor Cell Fate Patterning in Caenorhabditis elegans

Abstract: Six initially equivalent, multipotential Vulval Precursor Cells (VPCs) in adopt distinct cell fates in a precise spatial pattern, with each fate associated with transcription of different target genes. The pattern is centered on a cell that adopts the "1°" fate through Epidermal Growth Factor Receptor (EGFR) activity, and produces a lateral signal composed of ligands that activate LIN-12/Notch in the two flanking VPCs to cause them to adopt "2°" fate. Here, we investigate orthologs of a transcription complex t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…Although ERK-mediated phosphorylation of LIN-1 converts it to an activator of 1°fate genes (Leight et al, 2015), for other target genes, LIN-1 may act solely as a repressor. For example, transcription of lateral Notch ligand genes (see below) does not require LIN-1 activation (Underwood et al, 2017). Furthermore, dissociation of the LIN-1/LIN-31 complex exposes a phosphorylation site in the transactivation domain of LIN-31 such that it also becomes an activator when phosphorylated by ERK ( Fig.…”
Section: Quantitative Analysis Of Ligand-receptor Complexesmentioning
confidence: 99%
“…Although ERK-mediated phosphorylation of LIN-1 converts it to an activator of 1°fate genes (Leight et al, 2015), for other target genes, LIN-1 may act solely as a repressor. For example, transcription of lateral Notch ligand genes (see below) does not require LIN-1 activation (Underwood et al, 2017). Furthermore, dissociation of the LIN-1/LIN-31 complex exposes a phosphorylation site in the transactivation domain of LIN-31 such that it also becomes an activator when phosphorylated by ERK ( Fig.…”
Section: Quantitative Analysis Of Ligand-receptor Complexesmentioning
confidence: 99%
“…In many organisms, the epidermal growth factor receptors (EGFR), one of families of the receptor tyrosine kinases (RTK), are known to regulate several biological processes by activating key downstream pathways including the MAPK pathway [26][27][28][29][43][44][45] . In planarians, Smed-egfr-3 is required for proper regeneration as well as for ERK activation (Fig.4) 24,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Literature has already described examples of the activation of EGFR signaling by ROS and the potential of EGFR in mediating MAPK signaling including ERK activation [24][25][26][27][28][29][30][31] . Additionally, the egr (early growth response) family of transcription factors is suggested to be a downstream target of EGFR signaling in planarian regeneration as well as in other models [32][33][34][35] .…”
Section: Smed-egfr-3 and Smed-egr-4 Silencing Impair Ros Production Amentioning
confidence: 99%
See 1 more Smart Citation
“…In C. elegans, the CDK-8 module acts in a highly pleiotropic fashion yet a P3.p division frequency phenotype was not previously reported. In the ventral epidermis, the CDK-8 module was shown to act at many other steps, contributing in the L1 stage to the fusion to hyp7 of anterior and posterior Pn.p cells (such as P2.p and P9.p) (Yoda et al, 2005), to the block of division of all VPCs in the L2 stage (Clayton et al, 2008) and to the level of induction of 2° and 1° VPC fates via cell-autonomous repression of EGF and Notch signalling in the L3 stage; these activities being mostly revealed in a sensitized genetic background (Moghal et al, 2003, Grants et al, 2016, Underwood et al, 2017. We found that mutation in three other genes encoding components of the CDK-8 module also increased P3.p division frequency in an otherwise wild-type genetic background ( Fig.…”
Section: Nature Of the Causal Mutationsmentioning
confidence: 99%